1992
DOI: 10.1113/jphysiol.1992.sp018938
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channels and regulation of proliferation of human melanoma cells.

Abstract: 1. Ion channels and their possible relation to cell proliferation have been studied in a human melanoma cell line (IGR 1). Membrane currents were recorded by the patch-clamp technique using the cell-attached, cell-free and whole-cell mode. Cell growth was monitored by counting the number of cells at different days after seeding and [3H]thymidine incorporation. 2. A voltage-dependent 10 pS non-inactivating potassium channel (delayed rectifier) is the most commonly observed ion channel in this type of human cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(123 citation statements)
references
References 20 publications
5
118
0
Order By: Relevance
“…Inhibition of K ϩ channels by pharmacological agents has been found to inhibit cell proliferation in normal human lymphocytes (18)(19)(20)(21), human melanoma cells (22,23), small cell lung cancer (24), breast (25), and prostate (26) cancer cells. The role of K ϩ channels in cellular proliferation has been thought to be indirect, by either the possible influence of K ϩ channels on the intracellular Ca 2ϩ concentration (27) or, alternatively, the control of cell volume via K ϩ channels (28).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of K ϩ channels by pharmacological agents has been found to inhibit cell proliferation in normal human lymphocytes (18)(19)(20)(21), human melanoma cells (22,23), small cell lung cancer (24), breast (25), and prostate (26) cancer cells. The role of K ϩ channels in cellular proliferation has been thought to be indirect, by either the possible influence of K ϩ channels on the intracellular Ca 2ϩ concentration (27) or, alternatively, the control of cell volume via K ϩ channels (28).…”
Section: Discussionmentioning
confidence: 99%
“…proliferation of multiple cell types, including normal lymphocytes, melanoma, breast and prostate cancer cell lines, and glial cells (43)(44)(45)(46)(47). Concordantly, some K ϩ channels are upregulated during tumorigenesis and are pro-oncogenic.…”
Section: Fig 5 Sustained Induction Of Mclca5 By Detachment In Immormentioning
confidence: 99%
“…Ion channels, including K þ channels, are important for cell cycle and cell proliferation and are found in a variety of cancer cells (Nilius and Wohlrab, 1992;Skryma et al, 1997;Ouadid-Ahidouch et al, 2000;Fraser et al, 2003;Parihar et al, 2003;Farias et al, 2004;Jager et al, 2004). It has been shown that K þ channels play a role in controlling proliferation and transformation of epithelial cells (Pardo et al, 1999).…”
Section: Introductionmentioning
confidence: 99%